Targeting CCRL2 enhances therapeutic outcomes in a tuberculosis mouse model - Wang, Tianyin; Quijada, Darla; Ahmedna, Taha; Castillo, Jennie Ruelas; Naji, Nour Sabiha; Peske, J David; Karakousis, Petros C.; Paul, Suman; Karantanos, Theodoros; Karanika, Styliani (Frontiers in Immunology, 2025)
Tuberculosis (TB) remains among the leading infectious causes of death. Due to the limited number of antimicrobials in the TB drug discovery pipeline, interest has developed in host-directed approaches to improve TB treatment outcomes. C-C motif chemokine-like receptor 2 (CCRL2) is a unique seven-transmembrane domain receptor that is upregulated by inflammatory signals and mediates leucocyte migration. However, little is known about its role in TB infection. Here, we show that Mycobacterium tuberculosis (Mtb) infection increases CCRL2 protein expression in macrophages in vitro and alveolar macrophages (AMs), dendritic cells (DCs) and neutrophils in mouse lungs. To target selectively CCRL2-expressing cells in vivo, we developed a novel mouse anti-CCRL2 antibody-drug conjugate (ADC) linked with the cytotoxic drug SG3249. We tested its adjunctive therapeutic efficacy against TB when combined with the first-line regimen for drug-susceptible TB (isoniazid, rifampin, pyrazinamide, ethambutol; RHZE). The anti-CCRL2 ADC treatment potentiated RHZE efficacy in Mtb-infected mice and decreased gross lung inflammation. CCRL2 expression in lung DCs and AMs was lower in mice receiving anti-CCRL2 ADC treatment+RHZE compared to those receiving RHZE alone or the control group, although the total innate cell populations did not differ across treatment groups. Interestingly, neutrophils were completely absent in the anti-CCRL2 ADC treatment + RHZE group, unlike in the other treatment groups. IFN-γ+-and IL17-α+-T-cell responses, which are associated with optimal TB control, were also elevated in the anti-CCRL2 ADC treatment + RHZE group. Our findings suggest that CCRL2-targeting approaches may improve TB treatment outcomes, possibly through selective killing of Mtb-infected innate immune cells.